ANALISIS ROA DAN ROE TERHADAP RETURN SAHAM DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING : Studi Kasus Perusahaan Sektor Semen yang Terdaftar di Indeks Saham Syariah Periode 2019-2022 - Suyatno, Maulana Ihsan Yusufi; Mustahidda, Rahmania; Astohar, Astohar (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to reveal the effect of the variable Return On Assets, Return On Equity on stock levels with stock prices as an intervening variable in cement sector companies listed on the Indonesian Sharia Stock Index. This study is a quantitative observational type. Researchers use secondary data sources, which are in the form of variables ROA, ROE, stock returns and stock prices in a collection of cement sector stocks registered at ISSI in 2019-2022. The purposive sampling technique was used in sampling, which obtained a number of four issuers as the object of study. Based on the analysis, the results show that ROA and ROE simultaneously do not have a direct and significant effect on stock returns with a significance ROA of 0.36 and ROE of 0.46. The results obtained have an indirect effect or through stock prices obtained ROA and ROE have a significant effect on stock returns with ROE (0.03<0.05) and ROA (0.001<0.05)